Native Aquatic and Wetland Plants: Cardinal Flower, Lobelia cardinalis - Kimberly A. Moore; Luci E. Fisher; Carl J. Della Torre; Lyn A. Gettys (EDIS)
This 3-page fact sheet discusses the classification, description, habitat, propagation, and use of cardinal flower, an aquatic perennial that is commonly found in stream banks and swamps. Written by Kimberly A. Moore, Luci E. Fisher, Carl J. Della Torre III, and Lyn A. Gettys, and published by the UF Department of Agronomy, December 2015.